OUTCOME OF SCLEROTHERAPY IN THE TREATMENT OF NON-HEALING VARICOSE ULCERS UNDER ULTRASOUND CONTROL - Muhammad Jamil; Rashid Usman; Aaiza Aman; Kishwar Ali; Rai Ahmad Khan Kharl (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE:  Varicose veins are the commonest vascular problem both in men and women worldwide. Lack of timely management, inadequate treatment, and maltreatment of varicose veins can lead to the development of nonhealing ulcers and affects the quality of life in terms of health. Surgery, heat therapy, chemical therapy, and endoscopic treatment are the options of treatment. Foam sclerotherapy is relatively a new technique being practiced all over the world and has promising results.The objective was to determine the outcomes of foam sclerotherapy in the treatment of non-healing varicose ulcers.METHODOLOGY:In this descriptive study, 240 patients with chronic leg ulcers with varicose veins had been managed with foam sclerotherapy under ultrasound and compression bandage. All patients were reviewed at 7 days, 1month, 3 months, 6 months, 1 year, and 18 months both clinically and radiologically with a doppler ultrasound to assess the ulcer healing rates.RESULTS:The overall healing after 04 weeks of foam sclerotherapy was 83%. Two hundred and twenty-nine patients (95.4%) with ulcers healed within 02 months of the start of ultrasound-guided foam sclerotherapy. Delayed healing occurred after four months in11 cases. All those cases had either previous varicose veins surgery or deep vein thrombosis,or extensive perforator disease. During 18 months of follow-up, seven patients showed recurrence with a mean symptom-free period of 07 months.CONCLUSION:Chronic venous ulcers treated with foam sclerotherapyunder ultrasound guidance are associated with a high healing rate and low recurrence rate.